Compliment Responses of Male and Female Students at Senior High School in Medan - Bayazid, Liza Muharina; Dirgeyasa, I Wayan; Natsir, Muhammad (Jurnal Bahasa dan Sastra, 2026)
This study examines how Indonesian senior high school students respond to compliments in English within an EFL context, with a focus on gender differences and sociocultural influences. Data were collected from 30 eleventh-grade students (15 males and 15 females) using a Discourse Completion Test covering four domains: appearance, ability, personality, and possessions. Responses were analyzed using Herbert’s taxonomy of compliment responses. The results show that agreement strategies overwhelmingly dominate (over 86%), with comment acceptance and appreciation tokens as the most frequent forms. Gender differences were evident but limited: female students tended to use more elaborated and interpersonal responses, while male students more often employed deflective strategies such as comment history and questioning. The use of religious expressions to reassign praise reflects the influence of local cultural values. These findings suggest that while existing frameworks remain useful, they require contextual adaptation. The study highlights the importance of integrating pragmatic competence into EFL instruction to enhance learners’ intercultural communication skills.